The outer dusty edge of accretion disks in active galactic nuclei - Landt, Hermine (Frontiers in Astronomy and Space Sciences, 2023)
Recent models for the inner structure of active galactic nuclei (AGN) aim at connecting the outer region of the accretion disk with the broad-line region and dusty torus through a radiatively accelerated, dusty outflow. Such an outflow not only requires the outer disk to be dusty and thus predicts disk sizes beyond the self-gravity limit but requires the presence of nuclear dust with favorable properties. Here, we investigate a large sample of type 1 AGN by near-infrared (near-IR) cross-dispersed spectroscopy with the aim to constrain the astrochemistry, location, and geometry of the nuclear hot dust region. Assuming a thermal equilibrium for optically thin dust, we derive the luminosity-based dust radius for different grain properties using our measurement of the temperature. We combine our results with independent dust radius measurements from reverberation mapping and interferometry, and show that large dust grains that can provide the necessary opacity for the outflow are ubiquitous in AGN. Using our estimates of the dust covering factor, we investigate the dust geometry using the effects of the accretion disk anisotropy. A flared disk-like structure for the hot dust is favored. Finally, we discuss the implication of our results for the dust radius-luminosity plane.